PHYSICAL PROPERTIES OF IRRIGATED SANDY AND TAKYR DESERT SOILS (Scientific journal of the Fergana State University, 2025)
The granulometric composition of sandy desert soils underwent sharp changes under the influence of irrigation, that is, silt particles brought by irrigation waters settled in the upper layers of the soil and led to the formation of loamy and light loamy mechanical composition in them. The predominance of large particles (>0.01) in these soils indicates that they belong to the group of young soils.    In our data, the physiologically active moisture in the 0-50 cm layer is 7-8% according to the formula FAN=DNS-CH, which means that these soils have maximum hygroscopicity, as well as a low wilting moisture rate.